"I wish they could have answered their phones": Mobile communication in mass shootings. Issue 7 (9th August 2019) - Cumiskey, Kathleen M.; Hjorth, Larissa
Abstract: Mobile and social media have progressively become vessels for manifesting death and dying in our everyday lives. This article investigates the visual nature of social mobile media as "affective witnessing" by analyzing mobile media use during the 12th June 2016 Orlando Pulse Nightclub shooting in Orlando Florida (USA). How mobile media serve as witnesses and companions in this tragedy is demonstrated through analyzing first-person accounts, police body cam footage, 911 transcripts and online social media posts. This analysis reveals how mobile communication complicates situational awareness during mass trauma while also playing an important role in processing loss.